2020
DOI: 10.3390/ijerph17176267
|View full text |Cite
|
Sign up to set email alerts
|

Incident Reporting System in an Italian University Hospital: A New Tool for Improving Patient Safety

Abstract: Clinical risk management constitutes a central element in the healthcare systems in relation to the reverberation that it establishes, and as regards the optimization of clinical outcomes for the patient. The starting point for a right clinical risk management is represented by the identification of non-conforming results. The aim of the study is to carry out a systematic analysis of all data received in the first three years of adoption of a reporting system, revealing the strengths and weaknesses. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Davide Ferorelli evaluated the incident reporting system for clinical risk management and found that the system can effectively reduce litigation between doctors and patients (41). At the same time, the scholar also proposed corresponding clinical risk management methods to measure the risk of psychiatric violence (42).…”
Section: Develop a Hospital Workplace Violence Risk Reporting Systemmentioning
confidence: 99%
“…Davide Ferorelli evaluated the incident reporting system for clinical risk management and found that the system can effectively reduce litigation between doctors and patients (41). At the same time, the scholar also proposed corresponding clinical risk management methods to measure the risk of psychiatric violence (42).…”
Section: Develop a Hospital Workplace Violence Risk Reporting Systemmentioning
confidence: 99%
“…And then, the number of hospital-related crimes was reduced by 10.8%, by August 2021 ( 8 ). According to the evidence from Italy, Ferorelli D et al also confirm that comprehensive measures can reduce aggression to the detriment of HWs such as reporting events ( 38 ) which could activate the most suitable measures to prevent attacks ( 39 ). These demonstrated that the existing measures against WPV are still very important and effective to fight against the PVV during the pandemic, and comprehensive measures (measures of IPC and against WPV) should be implemented to mitigate hazards and protect the health, safety, and well-being of health workers.…”
Section: Discussionmentioning
confidence: 99%
“…However, it became apparent that one's safety performance and role as a HCP in the hospital system were only superficially reflected upon, and the organization and management were described as playing a more important role. The organization should establish rules for constant compliance with high safety standards (e.g., using critical incident reporting systems, standardized handovers, safety rounds and speak up initiatives [35,36]) and checking them was a particular focus for the HCPs who work in nursing. Rules, checklists, and standards for nursing and physicians must be more strictly observed and verified by the management to improve safety performance.…”
Section: Discussionmentioning
confidence: 99%